Analysis of the Ukrainian legislation on labour protection adaptation to the European Union acts (Law and Safety, 2023)
The decision of the European Council dated 23 June 2022 to grant Ukraine the status of an EU candidate became a significant incentive for reforms in the country. Reforming labour protection legislation is one of the most urgent tasks for the successful completion of Ukraine’s European integration and for the development of the country’s economy.The purpose of the article is to study the state of adaptation of Ukrainian legislation in the field of labour protection, in particular, occupational safety and health as well as employees’ health protection, to the legislation of the European Union. To achieve this goal, the general scientific and special scientific methods were used, in particular, dialectical, formal and logical, and comparative legal methods.The state of implementation of the provisions of the main European directives relating to occupational health and safety in the workplace into Ukrainian legislation is analysed. It has been established that by the beginning of 2023, the provisions of the analysed directives have been implemented only partially, since a significant part of the provisions has not been implemented into Ukrainian labour protection legislation.On the basis of the study, there have been identified factors that negatively affect the implementation process. Recommendations for improving the efficiency and effectiveness of the implementation of EU acts into Ukrainian legislation have been proposed. The adoption of the necessary regulatory legal acts in the field of labour protection to harmonise Ukrainian legislation with the European one has been substantiated.The process of Ukrainian legislation adaptation to EU norms requires coordinated cooperation between all branches of government for effective work and successful implementation of their rule-making and law enforcement powers in practice. The main focus of the ongoing process of Ukraine's legislative approximation with the EU should not be on the implementation of individual directives, but on the transfer of the overall architecture of EU legislation on health and safety, starting with the alignment with Framework Directive № 89/391/ЄЕС. In order to create a national state legal system that complies with EU norms, it is necessary to simultaneously adapt existing laws and adopt new legislative acts that comply with the European legal framework.
Keywords: labour protection legislation; occupational safety and health; adaptation of Ukrainian legislation; directive; implementation of European standards.